2001
DOI: 10.1002/ana.10055
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar ataxia type 2 presenting as familial levodopa‐responsive parkinsonism

Abstract: A genetic analysis identified 2 patients, approximately one-tenth of our patients with familial parkinsonism, who had expanded trinucleotide repeats in SCA2 genes. The reduction of 18F-dopa distribution in both the putamen and caudate nuclei confirmed that the nigrostriatal dopaminergic system was involved in parkinsonian patients with SCA2 mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 16 publications
10
75
1
Order By: Relevance
“…However, a close follow-up of these cases to see any development of cerebellar dysfunction or atypical features in the future, and further study in a large scale of SCA3 genetic screening in PD are needed to clarify the contribution of borderline expansion of SCA3 gene in the causes of PD. Since the first report of SCA2 gene mutation found in a large Chinese family with parkinsonism [Gwinn-Hardy et al, 2000], a serious of subsequent studies demonstrated that the mutation frequency of SCA2 in familial PD is around 10% [Shan et al, 2001;Lu, 2004a] and 0.4% for sporadic PD [Shan, 2004] in Taiwanese ethnic Chinese (Table II). In Singapore, SCA2 mutation rate in Chinese population is about 2.2% in early-onset sporadic PD [Lim et al, 2006].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, a close follow-up of these cases to see any development of cerebellar dysfunction or atypical features in the future, and further study in a large scale of SCA3 genetic screening in PD are needed to clarify the contribution of borderline expansion of SCA3 gene in the causes of PD. Since the first report of SCA2 gene mutation found in a large Chinese family with parkinsonism [Gwinn-Hardy et al, 2000], a serious of subsequent studies demonstrated that the mutation frequency of SCA2 in familial PD is around 10% [Shan et al, 2001;Lu, 2004a] and 0.4% for sporadic PD [Shan, 2004] in Taiwanese ethnic Chinese (Table II). In Singapore, SCA2 mutation rate in Chinese population is about 2.2% in early-onset sporadic PD [Lim et al, 2006].…”
Section: Discussionmentioning
confidence: 98%
“…Genetic factors such as a-synuclein, parkin, ubiquitin C-terminal hydrolase, DJ-1, and PINK-1 genes are thought to contribute to its cause [Polymeropoulos et al, 1997;Kitada et al, 1998;Leroy et al, 1998;Bonifati et al, 2003;Valente et al, 2004]. Recently, patients with spinocerebellar ataxia type 2 disorder (SCA2) or with Machado-Joseph disease (SCA3) were reported to have the phenotype of dopa-responsive parkinsonism without obvious cerebellar signs [Gwinn-Hardy et al, 2000Shan et al, 2001;Furtado et al, 2002;Lu et al, 2002;Payami et al, 2003]. Shan et al [2001] described two Chinese patients from Taiwan with SCA2 who presented at the age of 50 years with a parkinsonian syndrome clinically identical to typical Parkinson disease (PD).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…12). The sign of dopamine-responsive just has been seen in some Chinese families 13,14 and some white families. 15,16 We described here a large family from Hubei, China, that showed primarily autosomal dominant inheritance of parkinsonism symptoms acrossing four generations.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, in people of African origin, ataxia with parkinsonism is common (2), and pure ataxia and clinically typical Parkinson's disease (4-6) represent the edges of the disease spectrum. SCA2 mutations usually present with a pure ataxia syndrome in Caucasians (7), but in many Chinese families, a phenotype that is almost indistinguishable from Parkinson's disease occurs (8)(9)(10). Likewise, the clinical phenotype of Dentatorubropallidoluysian Atrophy in Japanese and European populations and that of Haw River syndrome in African Americans were disparate enough to hide the fact that these diseases were caused by the same mutation (11,12).…”
Section: Ethnic Differences and Disease Phenotypesmentioning
confidence: 99%